A 32‐year‐old Woman Diagnosed with 22q11.2 Deletion Syndrome and Complicated by Hypothyroidism. Issue 1 (27th June 2014) - Sasaki, Yosuke; Obara, Haruo; Shimabukuro, Akira
Abstract : 22q11.2 deletion syndrome (22qDS) resulting from a microdeletion of 22q11.2, is usually diagnosed in the postnatal period, and generally manifests as various combinations of cardiac defects, hypoparathyroidism, facial dysmorphism, palate deformity and cellular immunodeficiency. We report a case of a 32‐year‐old woman presenting with seizures and hypocalcemia, who was diagnosed with 22qDS, along with a literature review of adult cases. Physicians should recognize the 22qDS in adults presenting with any combinations of hypocalcemia, hypothyroidism, cardiac defects and psychiatric disorders. Pathognomonic facial dysmorphism or short stature can be the key to diagnosis.